(3bQGAI CHj YeQh Hf GdYdGAs - (3YHO Gddg Hf eMeO Hf YHO Gddg GdbQajs
(3ChdgG (B:s
(3hHYO abO QZH Edi HYV GdENhGf GdeYJfjf HJdGhg GdbQBf Cf CaQO dage s
(3BNQgG (B:s
(3bdJ bGd eMeO Hf YjSi aLejY YOO GdCi Ydi ePgH Cgd GdeO JeJ GdQhGjI HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B79s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
(3eUOQ GbJfGA GdCUd (B:s
(3ajV Gddg (B(213) s
Keywords: (3GdbQGAGJ hGdJLhjOs